MENA Quarterly Economic Brief, January 2016 : The Economic Effects of War and Peace - Devarajan, Shantayanan; Mottaghi, Lili (Washington, DC: World Bank, 2016)
This report estimates economic growth in the Middle East and North Africa (MENA) to fall short of expectations, at 2.6 percent in 2015, below the 2.8 percent predicted in October. Being constrained by war, terrorism and to some extent cheap oil, short term growth prospects in MENA remain “cautiously pessimistic.” Not only have the civil wars caused untold damage to human and physical capital, in Yemen the number of poor people has almost doubled after the war, but they have created one of the biggest forced displacement crises since World War II. The report examines the different ways in which civil wars are affecting the economies of the region, including the important channel of forced displacement. We also explore how economic fortunes will turn around if there is peace. A peace settlement in the war-torn Syria, Iraq, Libya and Yemen could lead to a swift rebound in oil output and exports, allowing them to increase fiscal space, improve current account balances and boost economic growth in the medium term with positive spillovers to the neighboring countries.